The Amount of Language Exposure Determines Nonlinguistic Tone Grouping Biases in Infants From a Bilingual Environment. Issue 2 (September 2014) - Molnar, Monika; Lallier, Marie; Carreiras, Manuel; Molnar, Monika; Sebastian‐Galles, Nuria
<x xml:space="preserve">Abstract</x> Duration‐based auditory grouping preferences are presumably shaped by language experience in adults and infants, unlike intensity‐based grouping that is governed by a universal bias of a loud‐soft preference. It has been proposed that duration‐based rhythmic grouping preferences develop as a function of native language phrasal prosody. Additionally, it has been suggested that phrasal prosody supports syntax acquisition (e.g., prosodic bootstrapping of word order within phrases). Using a looking preference procedure, in the current study, 9‐to‐10‐month‐old Spanish‐dominant and Basque‐dominant bilingual infants' rhythmic preferences in response to nonlinguistic tones alternating in duration or intensity were assessed. In the intensity‐based condition no effects of language experience was present. In the duration‐based condition, however, infants exhibited grouping patterns as predicted by the phrasal prosody of their dominant input. Considering the proposed link between syntactic bootstrapping and perceptual tone grouping, our overall results suggest that syntax acquisition (e.g., learning the rules of word order) is supported by different auditory perceptual mechanisms for the dominant syntax than for the less dominant syntax in the infant's dual language input.